Razvoj medicinske rehabilitacije v Sloveniji in Ljubljani - Zupanič Slavec, Zvonka (Zdravniški vestnik, 2013)
Even in ancient times, people found empirically that natural hot springs had a healing effect on ill or injured people. This knowledge was passed on through Antiquity and the Middle Ages to the present, when these discoveries have gained a scientific basis. This knowledge was further enhanced by the recognition that successful treatment and rehabilitation require patients to be physically active. In modern times, this led to the development of a new healthcare profession: physiotherapy. At the beginning of the twentieth century, physicians realized that long-term immobilization of patients in beds was harmful and that they needed to get up and start moving as soon as possible. This task was performed by physiotherapists. In Slovenia, certain spas have been known since Antiquity, and in the nineteenth century some of these were developed into health spas (Laško, Rimske Toplice, Dobrna, and others), where centuries of experience were put to use. The first institution in Slovenia to introduce physiotherapy for the hospital treatment of patients was the Šlajmer Sanatorium in Ljubljana in 1940. After the Second World War, many disabled people of all ages needed a new kind of hospital to address their physical, psychological, and social reintegration into everyday life and work. Following an initiative from orthopedists, the Soča Rehabilitation Institute for the Disabled was founded in 1954 in Ljubljana. Prior to this, it had already functioned as a section of the University Hospital of Orthopedics. It became the central institution for rehabilitation of sick and injured patients, and also a teaching base for related healthcare professions, training physiotherapists, occupational therapists, and doctors specializing in physical and rehabilitation medicine. The article further presents the development of hospital-based rehabilitation at the University Medical Centre in Ljubljana.
Keywords: fizikalna in rehabilitacijska medicina; history of medicine; institutions for the rehabilitation of the disabled; physical and rehabilitation medicine; Slovenia; Slovenija; zavodi za rehabilitacijo invalidov; zgodovina medicine